Framing Media Islam Online atas Konflik Keagamaan di Indonesia - Rusmulyad, Rusmulyad (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2013)
cannot break away from the ideological background or vi–sion of their own umbrella institution, so that the construc–tion of reality just follows the interest each has. By using Gamson’s and Modigliani’s tools of framing analysis, this paper analyzes how three Islamic media, namely arrahmah. com, voa-islam.com and hidayatullah.com, construct the re–ligious conflicts that occurred in Indonesia from 2011 to early 2012 in their own news-making. The results suggest that in news-making of religious conflicts, those three online media tended to do news-framing vulgarly, sarcastically, and provocatively.Keywords: online Islamic media, news, religious conflict, framing.—————————————————————————Ketika media memberitakan peristiwa atau isu tertentu, seringkali media tidak dapat melepaskan diri dari latar ideologi atau visi lembaga, sehingga konstruksi atas realitas yang terbangun juga cenderung mengikuti perspektif yang dimiliki masing-masing media. Dengan menggunakan analisis framing dari Gamson dan Modigliani, tulisan ini mengulas bagaimana tiga media Islam online, yakni arrahmah.com, voa-islam.com dan hidayatullah.com meng–konstruksi atau mengemas pemberitaan seputar konflik keagamaan di Indonesia dalam kurun 2011 hingga awal 2012. Hasil studi ini menyatakan bahwa dalam melakukan pewartaan atau membuat berita konflik keagamaan, ketiga media online tersebut telah melakukan pembingkaian (fra–ming) yang cenderung vulgar, sarkas dan provokatif.Kata Kunci: media Islam online, berita, konflik keagamaan, framing.